The role of frailty in advanced HF and cardiac transplantation - Bart, Nicole K.; Powell, Alice; Macdonald, Peter S. (Frontiers in Cardiovascular Medicine, 2023)
Frailty is a complex, multi-system condition often associated with multimorbidity. It has become an important prognostic maker across a range of conditions and is particularly relevant in patients with cardiovascular disease. Frailty encompasses a range of domains including, physical, psychological, and social. There are currently a range of validated tools available to measure frailty. It is an especially important measurement in advanced heart failure, because frailty occurs in up to 50% of heart failure patients and is potentially reversible with therapies such as mechanical circulatory support and transplantation. Moreover, frailty is dynamic, and therefore serial measurements are important. This review delves into the measurement of frailty, mechanisms, and its role in different cardiovascular cohorts. Understanding frailty will help determine patients that will benefit from therapies, as well as prognosticate outcomes.